SOSIALISASI PENTINGNYA PROSEDUR KERJA PENGELOLAAN REKAM MEDIS TEBAL (VOLUMENIOUS BULKY) DI RSKJ SOEPRAPTO PROVINSI BENGKULU - Nofri Heltiani; Ismail Arifin; Khairunnisyah Khairunnisyah; Liza Putri (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
Volumenious bulky medical records are one of the problems that often occur in storage and in circumstances where the medical records of patients with certain diseases who routinely go on an outpatient basis or are treated for a long time and routinely become very thick because the patient's entire medical history is stored in one folder. Based on the results of the research that has been done, it is known that the Soeprapto Social Hospital in Bengkulu Province does not have standard medical record thickness and work procedures for volumenious bulky medical record management. The purpose of this Community Service activity is to create a culture of using work procedures as a guideline for procedures or stages in managing volumenious bulky medical records. Community Service activities are carried out for 2 months, from November to December 2022 at the Soeprapto Social Hospital in Bengkulu Province with 10 participants. The method used in this Community Service activity is community education through socialization/counseling and training by demonstrating the use of work procedures for volumenious bulky medical record management. Socialization/ extension and training on the use of volumenious bulky medical record work procedures for filing officers at the Soeprapto Social Hospital in Bengkulu Province went well. Understanding in the application of work procedures can be implemented. After the PKM activities have been carried out, the Soeprapto Social Hospital in Bengkulu Province plans to evaluate the use of these work procedures in stages according to patient visits.